RISK MANAGEMENT AND ITS INFLUENCE OF INSURANCE COMPANY - FLOREA IANC MARIA MIRABELA; LĂPĂDUŞI MIHAELA LOREDANA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
The Risk Management summarizes the essence of insurance business. The effectiveness of risk management is on the correct definition and risk best estimates which provide a reliable basis for the dissipation or its transfer through insurance. In this regard, identifying exposure to insured damage constiruie an important stages as influences concrete ways to prevent and control the risk. Analysis and quantification of the risk should provide solid support for drafting the insurance contract